Mobile patient appoinment and helping system for emergency - Chang, Ling Shing (2015)
With the advancement of information technology, the use of information and communication technology has covered every aspect of the life. Unfortunately, Many of hospitals in Malaysia still using the manual management of their patient and appointment records. After registering the appointment manually at counter hospital, the patients have to waste their time for waiting at the hospital. Thus to reduce the waiting time at the hospital, a Mobile Patient Appointment and Helping System for Emergency is developed to overcome this serious problem. The system will provide an updated information about the doctors and services in the hostpitals. The system is implemented using Android to be easyn to use any time and any place. In this project, the Hypertext Preprocessor (PHP) is used as the main programming language for developing the system. Whlile some other open source web technologies such as Hypertext Markup Language 5 (HTML5), Cascading Style Sheets (CSS) and JavaScript (JS) are also used to enhances the functionality and usability of this web based application. In short, this project will be used to improve the daily hospital services and operations of all hospitals.